Effects of canagliflozin on body weight and body composition in patients with type 2 diabetes over 104 weeks. Issue 4 (18th May 2016) - Blonde, Lawrence; Stenlöf, Kaj; Fung, Albert; Xie, John; Canovatchel, William; Meininger, Gary
ABSTRACT: Objectives : Canagliflozin, a sodium glucose co-transporter 2 (SGLT2) inhibitor, has been associated with weight loss in a broad range of patients with type 2 diabetes mellitus (T2DM). This analysis further evaluated changes in body weight and composition with canagliflozin in two 104-week, Phase 3 studies. Methods : In Study 1, patients aged 18–80 years (N = 1, 450) received canagliflozin 100 or 300 mg or glimepiride as add-on to metformin for a 52-week core treatment period, followed by a 52-week extension period. In Study 2, patients aged 55–80 years (N = 714) received canagliflozin 100 or 300 mg or placebo added to stable background antihyperglycemic agents for a 26-week core treatment period, followed by a 78-week extension period. Percent change from baseline in body weight; proportion of patients with any weight loss, ≥5% weight loss, and ≥10% weight loss; change in body mass index (BMI) and waist circumference; change in body weight across weight-loss quartiles; and changes in body composition were evaluated in both studies. Results : Canagliflozin 100 and 300 mg provided sustained weight loss versus either glimepiride or placebo over 104 weeks. More patients experienced any weight loss and ≥5% weight loss with canagliflozin versus comparator. Across the 3 highest weight-loss quartiles, canagliflozin provided greater weight loss versus glimepiride or placebo. BMI and waist circumference reductions were observed with canagliflozin 100 and 300 mg versus either glimepiride or placebo over 104 weeks; more patients had BMI or waist circumference reductions with canagliflozin versus comparator. Body composition analysis indicated that the majority of weight loss was due to loss of fat mass. Canagliflozin was generally well tolerated, with increased incidence of adverse events related to the SGLT2 inhibition mechanism. Conclusions : Canagliflozin 100 and 300 mg provided sustained reductions in body weight, BMI, and waist circumference in a greater proportion of patients with T2DM versus glimepiride or placebo over 104 weeks. Trial registration : ClinicalTrials.gov NCT00968812, NCT01106651